Наративні стратегії у романі Карама Сабера "Святиня" - Рибалкін, Сергій Валерійович (Київський національний університет імені Тараса Шевченка, 2024)
Дослідження фокусується на лінгвістичному аналізі наративних стратегій у романі Карама Сабера «Святиня», зокрема на мовних засобах створення багатошарового наративу. Спираючись на методологічні принципи аналізу текстів, розроблені К. М. Тищенком, та його фундаментальні дослідження арабсько-українських мовних контактів, розглядаються лексико-стилістичні та синтаксичні особливості оповідної структури твору. Результати дослідження розширюють розуміння лінгвістичних механізмів створення магічно-реалістичного наративу в сучасній арабській літературі.

The research focuses on the linguistic analysis of narrative strategies in Karam Saber’s novel “The Shrine”, particularly examining the linguistic means of creating a multilayered narrative. Drawing upon the methodological principles of textual analysis developed by K. M. Tyshchenko and his fundamental studies of Arabic-Ukrainian language contacts, the study investigates the lexical-stylistic and syntactic features of the narrative structure. The subject of research encompasses the linguistic characteristics of different narrator types and the means of implementing focalisation that facilitate the interaction between realistic and magical-realistic narrative planes.
Narrative Strategies in Karam Saber’s Novel "The Shrine"
Keywords: арабська проза; лінгвістичні засоби; магічний реалізм; наративні стратегії; фокалізація; хронотоп; Arabic prose; chronotope; focalization; linguistic means; magical realism; narrative strategies